Manguni and Christian Nationalism (in) Minahasa - Denni H.R. Pinontoan (State Islamic Institute of Manado (IAIN) Manado, Indonesia, 2020)
This article describes the process and meaning of the reconstruction of Manguni, as the sacred bird in the old Minahasa religion which became a symbol of Gereja Masehi Injili in Minahasa (GMIM) in the context of colonialism. In particular, that thing to be discussed is the reconstruction of meaning, from Manguni as a mythological belief to Manguni as an ecclesiastical symbolic motive that carries a message of nationalism. Since the early of 20th century, the historical context and discourse of the Minahasa Christian intellectuals have been the subject of research to trace the development of Christian nationalism (in) Minahasa. In the context of GMIM, the interesting things are constituted as the dialogues and debates in colonial church forums, namely the Indische Kerk delivered by Christian leaders. This articles shows that, as a reaction to colonialism whic has changed many things predominantly in Christan Minahasa society, nationalism has grown and developed uniquely through discourse of community elites and church leaders. The expression of nationalism is through political and ecclesiastical path, which both of them use the legacy of religious tradition as tool of negotiation, namely the symbol of the institution with the motive of Manguni bird.